Early Islam in Nusantara: The First Trace of Islam through the Spices Trade - Farid, Muhammad (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2021)
Abstract The history of the entrance of Islam became the most important and the most obscure event in the discourse of Indonesian history. The authors note two fundamental problems concerning this